The Use of Code-Mixing and Code-Switching: Challenge Identification in Language Online Mass Media - Susanti, Ratna; Haryanto , Haryanto; Pranawukir, Iswahyu; Safar, Muh; Tjahyadi, Indra (Center of Language and Cultural Studies [CLCS], 2024)
This study is aimed at investigating types of code-mixing and code-switching as challenges in language identification in online mass media. Journalists mostly mix language to emphasize particular topics and to reiterate them as well. It becomes a challenging task to identify automatic language used with special language. It is focused on articles published in the mass media in Tempo Magazine 2023, in which the media illustrate Indonesian news, the economy, and politics. The method of qualitative research is used to describe the use of code-mixing and code-switching as challenge identification in mass media with documentary techniques. The technique conducted involves reading, studying, identifying, classifying, and analyzing data. Codified standardized English proposes intra-sentential switching, inter-sentential switching, tag switching, and intra-word switching. Meanwhile, the types of code-mixing, insertion, alternation, and congruent lexicalization are identified and analyzed. The data analysis used a process of organizing, analyzing, and interpreting qualitative data into code-switching and code-mixing classifications. The study result is found that 14 code-mixing and code-switching were found